The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/jas/sky077
|View full text |Cite
|
Sign up to set email alerts
|

Administration of recombinant bovine somatotropin prior to fixed-time artificial insemination and the effects on fertility, embryo, and fetal size in beef heifers

Abstract: Our objectives were to determine the effects of the administration of recombinant bovine somatotropin (bST) at the initiation of a fixed-time AI (TAI) protocol on concentrations of plasma IGF-1, follicle diameter, embryo/fetal size, and pregnancy rates in replacement beef heifers. Four hundred and fourteen Angus-based beef heifers were enrolled in a completely randomized design at 4 locations from January to July of 2016. All heifers were exposed to the 7-d CO-Synch + controlled internal drug release (CIDR) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Concentrations of P4, insulin [ 26 , 27 ], and IGF-1 [ 28 , 29 , 30 ] were analyzed by competitive chemiluminescent immunoassay using the Immulite 1000 (Siemens, Los Angeles, CA, USA). A 50 µL sample of maternal serum and all controls were analyzed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of P4, insulin [ 26 , 27 ], and IGF-1 [ 28 , 29 , 30 ] were analyzed by competitive chemiluminescent immunoassay using the Immulite 1000 (Siemens, Los Angeles, CA, USA). A 50 µL sample of maternal serum and all controls were analyzed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with rbST did not increase the size of the ovulatory follicle 48 h after the removal of the PRID (day 10) [14,15]. In a study with Holstein cows in Brazil, the ovulatory diameter was greater for cows treated with rbST (18.2 mm) compared to the control group (15 mm) [5].…”
Section: Discussionmentioning
confidence: 93%
“…The rbST has been associated with a higher growth rate of the conceptus and consequently with an increase in pregnancy rate [9,28,29]. However, other studies report that the effect of rbST on the total pregnancy rate has not been observed [2,15]; or even a negative effect of rbST on reproduction, whereby cows treated with rbST had a decreased conception rate [31].…”
Section: Discussionmentioning
confidence: 99%
“…In humans it is used to treat multiple sclerosis. Thyrotropin releasing hormone is used to diagnose hypothyroidism and pituitary pars intermedia dysfunction (PPID) by administering the hormone to animals and observing the response . Oxytocin is a naturally occurring hormone that is used to stimulate uterine contractions in animals, as it is in humans.…”
Section: Other Drug Classesmentioning
confidence: 99%
“…Thyrotropin releasing hormone is used to diagnose hypothyroidism and pituitary pars intermedia dysfunction (PPID) by administering the hormone to animals and observing the response. 134 Oxytocin is a naturally occurring hormone that is used to stimulate uterine contractions in animals, as it is in humans. Both human and porcine insulins are approved for use in veterinary medicine with the two insulin structures differing by a single residue.…”
Section: ■ Analysis Of 3d Descriptors and Shapementioning
confidence: 99%